PERSEPSI MAHASISWA TERHADAP PENERAPAN AKUNTANSI SYARI’AH PADA KURIKULUM AKUNTANSI ( STUDI KASUS MAHASISWA PRODI AKUNTANSI UNRIKA BATAM) - Rumawi R; Firdaus Hamta (EQUILIBIRIA, 2015)
Perception is the process of information processing environment in the form of stimulus, which is received through the sensory organs and transmitted to the brain to be selected, organized, giving rise to the interpretation or assessment inprestation form of sensing or previous experience. The research was conducted at the University Student Accounting Department Batam Riau Islands, the VI and VIII semester students become informants (sample), conducted qualitatively by waive the amount of information (sample) but the information (data)be gathered until data saturation.  Results of the research that students in the study sharia accounting, generally can accept and be open. Students' perceptions of acceptable accounting sharia for several reasons such as adding new knowledge and indeed syariah existing accounting environment around the community. In the learning process syariah accounting on the situation that exists today, generally require methods that are practical and necessary to add more time or special time broader and based applications (practice). However, students generally recognize gain new knowledge in particular on syariah accounting, such as accounting can distinguish with conventional and syariah accounting is considered humane.